Exercise in Water Provides Better Cardiac Energy Efficiency Than on Land - Fukuie, Marina; Hoshi, Daisuke; Hashitomi, Tatsuya; Watanabe, Koichi; Tarumi, Takashi; Sugawara, Jun (Frontiers in Cardiovascular Medicine, 2021)
Abstract Although water-based exercise is one of the most recommended forms of physical activity, little information is available regarding its influence on cardiac workload and myocardial oxygen supply-to-demand. To address this question, we compared subendocardial viability ratio (SEVR, the ratio of myocardial oxygen supply-to-demand), cardiac inotropy (via the maximum rate of aortic pressure rise [dP/dTmax]), and stroke volume (SV, via Modelflow method) responses between water- and land-based exercise. Eleven healthy men aged 24±1 years underwent mild- to moderate-intensity cycling exercise in water (WC) and on land (LC) consecutively on separate days. In WC, cardiorespiratory variables were monitored during leg cycling exercise (30, 45, and 60 rpm of cadence for 5 minutes each) using an immersible stationary bicycle. In LC, each participant performed cycling exercise at the oxygen consumption (VO2) matched to the WC. SEVR and dP/dTmax were obtained by pulse wave analysis from peripheral arterial pressure waveforms. With increasing exercise intensity, SEVR exhibited similar progressive reductions in WC (from 211±44 to 75±11%) and LC (from 215±34 to 78±9%) (intensity effect: P<0.001) without their conditional differences. WC showed higher SV at rest and a smaller increase in SV than LC (environment-intensity interaction: P=0.009). The main effect of environment on SV was significant (P=0.002), but that of dP/dTmax was not (P=0.155). SV was correlated with dP/dTmax (r=0.717, P<0.001). When analysis of covariance (ANCOVA) was performed with dP/dTmax as a covariate, the environment effect on SV was still significant (P<0.001), although environment-intensity interaction was abolished (P=0.543). These results suggest that water-based exercise does not elicit unfavorable myocardial oxygen supply-to-demand balance at mild-to-moderate intensity compared with land-based exercise. Rather, water-based exercise may achieve higher SV and better myocardial energy efficiency than land-based exercise, even at the same inotropic force.